Apocalypticism in Shi'a and Jewish Eschatology: A Comparative Analysis of the Historical Chronology of the End Times - Hidayat Nurrohman; Mahmud Muhsinin; Muhammad Wahid Nur Tualeka (Al-Adyan: Journal of Religious Studies, 2026)
Apocalypticism is an important aspect of the eschatological traditions in both Shi’a and Jewish thought. Both traditions contain end-time narratives characterized by crisis, divine intervention, and the establishment of a new world order. This study aims to examine apocalypticism in Shi’a and Jewish eschatology through a comparative analysis of the historical chronology of the end times. This research employs a qualitative method using library research within the perspective of religious studies. The primary sources include Shi’a hadith literature, particularly Bihar al-Anwar, as well as apocalyptic texts in the Tanakh such as the Books of Daniel, Ezekiel, Isaiah, and Zechariah. The analysis is based on the apocalyptic theory of John J. Collins, which emphasizes the pattern of historical crisis, divine intervention, and world transformation.The findings show that both Shi’a and Jewish traditions share a similar apocalyptic structure, namely a progression from moral decay and historical crisis toward divine restoration and a new world order. However, differences appear in the central figures and forms of divine intervention. Shi’a eschatology emphasizes the role of Imam Mahdi and Prophet Jesus (Isa AS) as messianic agents, while Jewish eschatology highlights direct divine intervention in restoring Israel and destroying evil forces. This study contributes to comparative eschatological studies by reconstructing scattered apocalyptic narratives into a coherent historical chronology based on Collins’ framework. It provides a structured analytical model for understanding fragmented eschatological texts across different religious traditions. Apokaliptisisme merupakan salah satu aspek penting dalam tradisi eskatologi Syiah dan Yahudi. Kedua tradisi tersebut memiliki narasi akhir zaman yang ditandai oleh krisis, intervensi ilahi, dan terbentuknya tatanan dunia baru. Penelitian ini bertujuan untuk mengkaji apokaliptisisme dalam eskatologi Syiah dan Yahudi melalui analisis komparatif terhadap kronologi historis akhir zaman. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kepustakaan (library research) dalam perspektif studi agama-agama. Sumber primer penelitian berasal dari hadis-hadis Syiah, khususnya Bihar al-Anwar, serta teks-teks apokaliptik dalam Tanakh seperti Kitab Daniel, Yehezkiel, Yesaya, dan Zakharia. Analisis penelitian menggunakan teori apokaliptisisme John J. Collins yang menekankan pola krisis historis, intervensi ilahi, dan transformasi dunia. Hasil penelitian menunjukkan bahwa tradisi Syiah dan Yahudi memiliki pola apokaliptik yang serupa, yaitu perjalanan dari krisis dan kerusakan moral menuju pemulihan ilahi dan tatanan dunia baru. Namun, terdapat perbedaan dalam figur sentral dan bentuk intervensi ilahi. Eskatologi Syiah menekankan peran Imam Mahdi dan Nabi Isa AS sebagai agen mesianik, sedangkan eskatologi Yahudi menonjolkan intervensi langsung Tuhan dalam memulihkan Israel dan menghancurkan kekuatan jahat. Penelitian ini memberikan kontribusi pada studi eskatologi komparatif dengan merekonstruksi narasi-narasi apokaliptik yang tersebar menjadi kronologi historis yang lebih sistematis berdasarkan kerangka John J. Collins. Dengan demikian, penelitian ini menawarkan model analitis untuk memahami teks-teks eskatologis yang bersifat fragmentaris dalam tradisi keagamaan yang berbeda.